On the spider genus Neonella (Araneae: Salticidae): new records and taxonomic notes for species from southern South America - Ott, Ricardo; Silva, Guilherme O.; Marta, Kimberly S.; Rodrigues, Everton N. L. (Zootaxa, 2015)
The genus Neonella Gertsch, 1936 contains 12 species with an exclusive New World distribution (World Spider Catalog 2015). The genus was proposed by Gertsch (1936) to include N. vinnula Gertsch, 1936 from Florida and Texas, USA. Remaining species were added by Galiano (1965, 1988, 1998) and, more recently, Edwards (2003), Ruiz & Brescovit (2004), and Ruiz et al. (2007).